Penggunaan kaedah algoritma genetik dalam permasalahan penjadualan PCB: kajian kes di industri elektronik - Zalinda Othman, (2010)
Production planning and scheduling functions play important roles in production especially to ensure the availability of manufacturing resources needed to accomplish production tasks. This paper proposes the use of Genetic Algorithm in solving scheduling problems and the case study has been conducted in printed circuit board assembly company. Genetic algorithm formulation included chromosome representations and genetic operators have been developed to suit the scheduling problems that take into account the alternative production lines. Simulation results have been compared to the manual schedules. It shown that the genetic algorithm is capable to produce schedules with shorter assembly time. It is can accommodate additional elements such as maintainance time quite easily. This is done by adding the maintenance time slot within the chromosome. Another experiment has been done by using dispatching rule in sequencing the models on the assembly lines. Genetic Algorithms have shown a promising results compared to manuan and dispatching rule